Analisis Pendidikan Islam dengan Pendekatan Psikologi Modern Terhadap Perilaku Beragama - Abzar, Muhammad Abzar; Rosadi, Khumaini (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2023)
This research examines psychology as an approach to Islamic studies, especially Islamic education. In fact, psychology and Islamic education have the same concepts and goals in looking at various problems in life, so that Islamic studies require psychological approaches, so that they can be more focused and clearer. This research is a library research, namely research sourced from library materials using a qualitative approach.Therefore, the method used in this research is an exploration of a number of data, both primary data and secondary data with the following concrete steps: reading and examining in depth primary data such as books which are the result of research, theses or dissertations related to psychology and Islamic education. Therefore, psychology as an approach can produce findings that are appropriate to the context.In Islamic studies, especially Islamic education, it can be access to other sciences to be used as a measuring tool in looking at various problems in society. This is what then led to the mixing of discussion and research in psychology and Islamic education, because by combining these two disciplines, Islamic educational psychology was born.